CyTOF reveals platelet subtype changes predicting the efficacy of combined immunotherapy and targeted therapy in liver cancer - Wang, Wenjing; Liu, Dan; Wang, Lilin; Aishan, Maimaitijiang Wubuli; Chen, Li; Zheng, Sujun; Lu, Junfeng (Frontiers in Immunology, 2025)
IntroductionImmune checkpoint inhibitors combined with angiogenesis inhibitors are currently the first-line treatment for liver cancer. However, some patients still exhibit poor therapeutic outcomes. Platelets, as a critical component of blood, play a significant role in liver cancer progression by influencing angiogenesis and the tumor immune microenvironment.MethodsIn our study, we utilized mass cytometry (CyTOF) to analyze surface proteins on platelets in the plasma of 23 liver cancer patients before and after receiving combined immunotherapy and targeted therapy. Patients were grouped based on treatment efficacy to compare platelet subpopulation differences.ResultsWe observed that CD107a+ and CD62P+ platelet subpopulations were reduced in liver cancer patients. In the progressive disease (PD) group, the CD29+ platelet subpopulation was elevated compared to other groups. Notably, this subpopulation decreased with tumor remission and increased with tumor progression.DiscussionOur findings highlight the heterogeneity of platelets in liver cancer patients and suggest that the CD29+ platelet subpopulation may serve as a predictive biomarker for the efficacy of combined immunotherapy and targeted therapy. Additionally, CD29+ platelets could represent a potential therapeutic target in future research.